Evaluation of predisposing factors, etiology, and clinical manifestations of childhood empyema thoracis at a tertiary care center of Odisha - Meher, Sitanshu Kumar; Mahapatra, Sanjay Kumar; Murmu, Sapan Kumar; Meher, Purnima (Indian Journal of Child Health, 2018)
Background: Empyema thoracis (ET) is a life-threatening disease often encountered in pediatric patients. In spite of all modern sophistication of medical sciences, this disease is chargeable for a high proportion of hospital admission and continues to require an important tool against them. Objective: The objective of this study is to evaluate the age-sex profile, predisposing factors, etiology, seasonal variation, and clinical manifestations of ET in children. Methods: A cross-sectional study was conducted in the department of pediatrics in Western Odisha. A total of 80 children, aged 0–14 years and diagnosed as ET, were enrolled in the study. After inclusion, a detailed history including demographical data, clinical examinations, and thorough investigations (hematological, biochemical, and radiological) was done as per pro forma prepared for the study. Pleural fluid was collected by thoracocentesis and examined for cultural sensitivity. Results: Most of the cases belonged to the age group of 0–5 years (60%), and male-female ratio was 3:2. Of 80, 50 (72.5%) patients were malnourished. The most common symptoms in all patients were fever (100%) and cough (90%). Intercostal tenderness (100%) was the most common clinical sign. Staphylococcus aureus (60%) was the predominant causative organism. Conclusions: The prognosis of childhood empyema depends on the age, nutritional status of the child, and bacterial agent causing empyema. Earlier diagnosis and adequate treatment of potential predisposing factors favor the good prognosis.